The Influence of the Problem Based Learning Model on the Scientific Attitudes and Science Learning Outcomes of Fifth Grade Elementary School Students - Vania Desiyanti; Ikhlasul Ardi Nugroho (Postgraduate, University of Mataram, 2024)
This research aims to determine the significant influence of the PBL model on the scientific attitudes and science learning outcomes of fifth grade elementary school students. The method used is quasi experimental design with pretest non-equivalent control group design. The research population was SDN Hugus II Kapanewon Sewon, Bantul Regency, with a sample of several class V students from SD Negeri 2 Blunyahan, SD Negeri 3 Jarakan, SD Negeri Jarakan, and SD Negeri Sawit. The experimental group used the PBL model in science learning. The normality test was carried out using Kolmogrov Smirnov, the homogeneity test was carried out using Levene's test, and the hypothesis test was carried out using the independent sample t-test and MANOVA. The research results show that PBL has a positive and significant effect on scientific attitudes with a value of (0.000 < 0.005) and on learning outcomes with a value of (0.000 < 0.005). Data analysis shows that there is a significant influence of the PBL model on students' scientific attitudes and science learning outcomes with a value of (0.000 < 0.005).